Efektivitas Model Pembelajaran Sets Metode Praktikum Pada Materi Pemanasan Global Dalam Meningkatkan Kemampuan Berpikir Kritis - Danty Kusmianty; Bayu Widiyanto; Mobinta Kusuma (Cakrawala: Jurnal Pendidikan, 2020)
This research aims to improve the ability of critical thinking learners with learning SETS practicum methods. The methods used in this research is quantitative research. This is the kind of research experiments. The research design used was pre test post test design. The population of the research was the students of Class VII. Samples were taken using the technique of sampling culture i.e. Class VII D totaled 32 child and Class VII E totaled 32. The instruments used are the form of test questions test the ability of critical thinking, question form to measure the response of the students against the model of learning and teaching method SETS the observation sheet. Analysis of the tested using T-test and test N-Gain. Based on the results of the analysis of the T test data obtained sig 2 tailed 0.00< 0.05 indicate an increased in critical thinking skills. The results of the N-Gain test in experimental class of 68% indicate quite effectively. It can be concluded that the SETS learning model practicum method is quite effective applied to learning and there is an increase in critical thinking skills in students.